Analisis Praktik Endorsement dan Review Produk oleh Influencer terhadap Transaksi Najasy di Media Sosial Perspektif Fikih Muamalah Kontemporer : Studi pada Produk Skincare Non-BPOM Tahun 2024 - Eli febriani; Yerna Wiza; Widi Nugraha; Aidil Alfin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the practice of product endorsement and reviews by social media influencers, particularly in promoting skincare products without BPOM distribution permits, through the lens of contemporary Islamic commercial jurisprudence (fiqh muamalah). In the digital era, marketing strategies have shifted significantly with influencers playing a key role in shaping consumer opinions and purchasing decisions. However, many endorsements omit legal information and promote products containing harmful substances. This research employs a qualitative approach through literature review, analyzing scholarly articles, fatwas, regulations, and official BPOM data. Findings indicate that promoting unregistered products may involve elements of najasy (fraud), gharar (uncertainty), and tadlis (concealment), which contradict the Islamic principles of honesty and transparency. Therefore, ethical guidelines rooted in Islamic law are essential to ensure fair, halal, and consumer-protective digital marketing practices.